Formulation And Development Of A Bilayer Sustained Released Tablets Of Isosorbide Mononitrate - MR. ASHISH A PAHADE; DR. MRS. V.M.JADHAV; MR. V.J.KADAM (International Journal of Pharma and Bio Sciences, 2010)
The present study was to a develop bilayer sustained release tablet of Isosorbide mononitrate, an anti-anginal organic nitrate vasodilator. The tablets were prepared by wet granulation method. Hydrophilic and hydrophobic matrix materials such as hydroxypropyl methylcellulose, and polyox were used, which can release the drug up to 24hrs in predetermined rate. Binder used was pvp k-30. The influence of hydrophilic and hydrophobic polymer and granulation technique was studied. The formulated tablet were also characterized by physical and chemical parameters such as for granules, angle of repose, bulk density, compressibility index, total porosity, and drug content and for the tablet thickness, hardness, diameter, weight variation test, drug content, friability, and in vitro release studies. The granules showed satisfactory flow properties, compressibility, and drug content. The invitro release rate profile showed the higher concentration of F6 polymer in tablet.